Analysis of the capital of an enterprise as the main factor of financial stability - Kishibayeva Б.; Jaxybekova Г. (Economic series of the Bulletin of L.N. Gumilyov ENU, 2023)
In modern conditions, the capital structure is a factor that directly affects the financial condition of the enterprise, its long-term solvency, profit and financial stability. The level of efficiency of the enterprise is mainly determined by the purposeful formation of the volume and structure of capital. They help to develop the strategy and tactics of the company development and create on their basis management plans and decisions . The article presents a methodology for analyzing the equity capital of Caspian Oil JSC, the country’s largest enterprise for the production and sale of carbon raw materials, using absolute and relative indicators. The main purpose of the study is to analyze the structure of equity and its correlation dependence, the sources of formation and assessment of the financial stability of the enterprise. In general, the correlation analysis has revealed the strongest dependence of the equity capital on the assets of the enterprise. The financial stability of the enterprise is characterized by a number of financial coefficients. The analysis has given the assessment of the level of financial stability of the enterprise for 2019-2021. The relevance of the study is explained by the need for a systematic assessment of the quality of equity in the market and the need for the existence of its subjects. The main objectives of the research is to study the meaning and necessity of analyzing the equity of an organization, to assess the dynamics and structure of sources of financing equity.